2018
DOI: 10.21521/mw.6072
|View full text |Cite
|
Sign up to set email alerts
|

Effect of balanced supplementary feeding in winter on qualitative and quantitative changes in the population of microbes colonizing the rumen of red deer

Abstract: Gnat S., Dziedzic R., Nowakiewicz A., Zięba P., Trościańczyk A., Majer-Dziedzic B., Ziółkowska G., Beeger S., Wójcik M.Effect of balanced supplementary feeding in winter on qualitative and quantitative changes in the population of microbes colonizing the rumen of red deer Summary Ruminants are a group of animals that process and assimilate their food in a unique manner. The functioning of the digestive tract of these animals is closely related to the abundance and composition of microbes in the forestomach, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
2
2
1
Order By: Relevance
“…Particularly the phylum Firmicutes was present in higher proportions in red deer in enclosures than in free‐ranging red deer. This is in concordance with a study in Poland in which red deer that were not fed with supplementary food during winter had a lower abundance of bacteria than red deer that were fed with supplementary food (Gnat et al 2018). Recent studies on the microbiota of silage (Duniere et al 2017, Peng et al 2018) have revealed that certain bacterial taxa within the Firmicutes increase during ensiling when aerobic spoilage occurs (Driehuis et al 2018).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Particularly the phylum Firmicutes was present in higher proportions in red deer in enclosures than in free‐ranging red deer. This is in concordance with a study in Poland in which red deer that were not fed with supplementary food during winter had a lower abundance of bacteria than red deer that were fed with supplementary food (Gnat et al 2018). Recent studies on the microbiota of silage (Duniere et al 2017, Peng et al 2018) have revealed that certain bacterial taxa within the Firmicutes increase during ensiling when aerobic spoilage occurs (Driehuis et al 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the close contact to humans at winter enclosures might also increase the likelihood of zoonosis transmission. In addition, in contrast to the vast amount of research on dietary effects on the human gut microbiota and dysbiosis‐associated diseases (David et al 2014, Althani et al 2016), surprisingly little work has been carried out on the impact of supplementary feeding on the gut bacterial community of our most abundant large herbivores (but see: Li et al 2017a, Gnat et al 2018).…”
mentioning
confidence: 99%
“…In our study, farmed deer did not differ for total rumen protozoa concentration from their wild conspecifics; however, they did for the community composition. The average total number of rumen protozoa (3.29 × 10 6 /mL of rumen fluid) in this study was higher than that reported by other studies on red deer [35,37,38], but similar to the number reported by Hobson et al [36]. Rumen fluid of farmed animals was characterized by a lower percentage of protozoa belonging to the Diplodininae subfamily, and by the presence of protozoa of the Isotrichidae family (or holotrichs), totally absent in wild animals; Entodiniinae and Epidininae protozoa were present at a similar concentration in the two groups, with the Entodininae subfamily having the highest concentration.…”
Section: Discussioncontrasting
confidence: 78%
“…Bacterial population in the rumen of domestic cattle occurs at a concentration of 10 10–11 cells/g of rumen content [34], while other authors reported a total count of 10 9 in red deer [35,36]. Our results show a concentration of anaerobic and aerobic bacteria in a range of 10 5–6 cells/g.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation